Strategic Competence: Bridging The Cross-Cultural Communication - Lila Musyanda (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: The writer of this article is interested in examining the strategic competence, i.e., the ability to solve communication problems an inadeÂquate command of the linguistic and sociocultural code because it, can contribute to the development of an overall communicative competence. The concept of strategic competence is within the general framework of interlanguage development. The article describes two basic types of communication strategies: reduction and achievement, concentrating parÂticularly on the use of achievement strategies at the discourse level for English learners to manage a communication across culture appropriately.